Characteristics of Chinese patients with primary Sjögren's syndrome: preliminary report of a multi-centre registration study. (January 2020) - Xu, D; Zhao, S; Li, Q; Wang, Y H; Zhao, J L; Li, M T; Zhao, Y; Zeng, X F
Background: We established a multi-centre online registry for primary Sjögren's syndrome (pSS) in China, and compared Chinese patients with those from other countries. Methods: Data were from 87 rheumatology centres in 27 provinces. All 2986 patients had pSS according to the 2002 American-European Consensus Group or the 2016 American College of Rheumatology/European League Against Rheumatism. All centres used the same methods. Data on demographics, clinical parameters, laboratory results, disease activity and treatments were examined. Results: The female:male ratio was 22.9:1, and the mean age at onset was 46.31 years. A total of 332 (11.1%) patients had thyroid disease, including hyperthyroidism (1.2%), hypothyroidism (6.0%) and subacute thyroiditis (3.9%). Dry eye had a prevalence of 68.59% in Chinese patients, 93.7–96% in European patients and 97.3% in American patients. Dry mouth had a prevalence of 86.5% in Chinese patients, 93.2–96% in European patients and 97.9% in American patients. Fewer Chinese than European patients had arthritis (6.9% vs. 15–19.3%). ANA positivity was 90.7% in Chinese, 81.3% in European and 77.6% in American patients. Anti-SSA antibody positivity was 84.6% in Chinese, 71% in European and 68.2% in American patients. The most commonly used drugs in Chinese patients were hydroxychloroquine ( n  = 1818; 67.5%), glucocorticoids ( n  = 1720; 63.9%) and total glucosides of paeony ( n  = 1120; 41.7%). Conclusions: This study provided information on the phenotypes of Chinese patients with pSS, and identified several differences with patients from other geographical regions.